ENHANCEMENT OF THE SOLUBILITY OF FAMOTIDINE SOLID DISPERSION USING NATURAL POLYMER BY SOLVENT EVAPORATION - ALKUFI, HUSSEIN K.; RASHID, ASMAA M. (International Journal of Applied Pharmaceutics, 2021)
Objective: The aims of the study to enhance solubility and dissolution of famotidine using natural polymer. Solubility study of a drug is one of the contributing factors of its oral bioavailability. The formulation of poorly soluble drugs for oral delivery presents a challenge to the formulation technologists. Methods: The present study has shown that it is possible to raise the solubility for poorly soluble drugs like famotidine, by preparing solid dispersion using natural water-soluble polymer (xyloglucan and hyaluronic acid) as solubilizer through solvent evaporation method. Physical mixture and solid dispersion of famotidine with xyloglucan (XG) or hyaluronic acid in a ratio of 1:1, 1:2, 1:3 were prepared. Solubility study, drug content, dissolution profile and compatibility study were performed for famotidine in solid dispersions XS1, XS2, XS3, HS4, HS5, HS6 as well as in physical mixtures at a ratio 1:1 for both polymer (XG and hyaluronic acid). Results: It was observed that solid dispersions of each drugs showed an increase in dissolution rate in comparison with its pure drug in the ratio of 1:1 (Drug: carrier). It can be concluded that with the care and proper use of xyloglucan, the solubility of drugs poorly soluble can be improved. The prepared solid dispersion showed improvement of drug solubility in all prepared formulas. The best result was obtained with formula XS1 (famotidine: xyloglucan at ratio 1:1) that showed 26 fold increase in solubility compared to the solubility of pure drug. Conclusion: The natural solid dispersion, increased wettability and reduced crystallinity of the drug which leads to improving solubility and dissolution.